2021
DOI: 10.1111/1467-8268.12469
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the impact of GDP on financial development: Evidence from heterogeneous panels

Abstract: This paper examines the nonlinear impact of real GDP per capita on financial development in a panel of 125 countries. It also determines the moderating effect of inflation on the impact of GDP on financial development. It employs the dynamic panel system generalized method of moments (GMM) and the dynamic common correlated effects (CCE) to do both panel and countryspecific analysis, as well as control for cross-sectional dependence, heterogeneity and endogeneity. This study shows that GDP has a positive impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 37 publications
5
26
0
1
Order By: Relevance
“…As a general approach to testing the finance–growth nexus, almost all of the recent studies assumed linearity and employed symmetric techniques such as cointegrating regressions, vector autoregressive, vector error-correction, autoregressive distributed lags, Granger causality, and ordinary least squares, whereas a few studies assumed non-linear relationships between the financial system and economic growth and applied asymmetric techniques. These authors are Ehigiamusoe and Narayanan (2019) , Tsagkanos et al. (2019) , and Shodipe and Shobande (2021) , who studied, respectively, in a wide-ranging economic context, Greece, and the U.S., but there is yet no study concerning the asymmetric effects of the financial system on economic growth in China, which is the fastest-growing economy in the world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a general approach to testing the finance–growth nexus, almost all of the recent studies assumed linearity and employed symmetric techniques such as cointegrating regressions, vector autoregressive, vector error-correction, autoregressive distributed lags, Granger causality, and ordinary least squares, whereas a few studies assumed non-linear relationships between the financial system and economic growth and applied asymmetric techniques. These authors are Ehigiamusoe and Narayanan (2019) , Tsagkanos et al. (2019) , and Shodipe and Shobande (2021) , who studied, respectively, in a wide-ranging economic context, Greece, and the U.S., but there is yet no study concerning the asymmetric effects of the financial system on economic growth in China, which is the fastest-growing economy in the world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Odhiambo (2007) found evidence to support the demand‐following hypothesis in Kenya and South Africa, whereas the supply‐leading hypothesis was supported in Tanzania. Gozgor (2015) found a unidirectional causal relationship from economic growth to financial development in 7 countries, and Ehigiamusoe et al (2021) reported that economic growth enhances financial development in 125 countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the tourism and financial sectors could be driven by expansion in economic activities, because rapid economic expansion could give rise to tourism infrastructure, education, and safety, which could attract more international tourists and revenue (Tang et al, 2019). Economic expansion could also boost financial development if it causes households and firms to increase their demands for financial products, services, intermediaries, and institutions that prompt the financial sector to embark on innovations and technology to meet the increased demand (Ehigiamusoe et al, 2021; Peia & Roszbach, 2015). This suggests that the causal relationship between financial development and economic growth, as well as between tourism and economic growth could go in either direction.…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu adanya hubungan antara tingkat inflasi dan pertumbuhan laba pada perusahaan secara signifikan (Ndubuisi, I, & JI, 2019). Tulisan lain menyebutkan bahwa inflasi memiliki efek negatif pada perkembangan keuangan dan profitabilitas perusahaan di negara-negara dengan inflasi tinggi dan menengah (Ehigiamusoe, Guptan, & Narayanan, 2019).…”
Section: Latar Belakangunclassified